REFLECTIONS ON POLICY-MAKING AND EVALUATION IN PUBLIC POLICY - Assumpcao, Flaviana C. V. P. M. [UNESP]; Goulart, Joana [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
This article is a reflection on the policy making and evaluation processes in Public Policy in the light of the work written by Howlett et al, and the understanding given by the authors researched by them on the cycles and subsystems that comprise the processes of Public Policy. To understand about the decision-making of these processes, we studied the author Lindblom, to figure out who the political actors are and how they influence the government's decision-making. About the Public Policy theory and its typologies, it was necessary to read TJ Lowi and his publication in 1964. Finally, we dealt on how to evaluate a Public Policy with the authors Maria Cecilia Barreira and Maria do Carmo Carvalho regarding the perspectives of evaluation of policies and social programs, Elizabeth Rico about the evaluation processes and Klauss Frey with regard to the conceptual reflections, assessments and their implication for the Brazilian political situation.
Keywords: Public Policy; Evaluation; Decision Making